2014
DOI: 10.1186/1475-2891-13-14
|View full text |Cite
|
Sign up to set email alerts
|

Health habits and other characteristics of dietary supplement users: a review

Abstract: Dietary supplements are used by half to two-thirds of American adults, and the evidence suggests that this usage is one component of a larger effort to develop a healthier lifestyle. Dietary supplement users tend on average to be better educated and to have somewhat higher incomes than nonusers, and these factors may contribute to their health-consciousness. Dietary supplement use also tends to be more prevalent among women than among men, and the prevalence of use increases with age in both men and women. Num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
165
3
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(206 citation statements)
references
References 23 publications
25
165
3
13
Order By: Relevance
“…Gleiche Assoziationen werden auch von Foote et al [19], Dickinson et al [25] und der CoLaus Studie aus der Schweiz [26] berichtet.…”
Section: Studiendesign Und Stichprobenunclassified
“…Gleiche Assoziationen werden auch von Foote et al [19], Dickinson et al [25] und der CoLaus Studie aus der Schweiz [26] berichtet.…”
Section: Studiendesign Und Stichprobenunclassified
“…If we add the measured overages, these 12 nutrients might be the most probable candidates for population nutrient overexposure (43). Many consumers take MVMs over years, and some combine MVM intake with the intake of higher dosage single vitamin or mineral DSs and highly fortified foods, and this raises safety concerns if the ULs are exceeded (4,43,44). NHANES 2003-2006 data indicated that although DS use reduced the percentage of adults ($19 y) below the Estimated Average Requirement for calcium; magnesium; and vitamins A, D, C, and E, it also increased the percentage of participants whose intake exceeded ULs for niacin, vitamin A, folate, iron, magnesium, and zinc (1).…”
Section: Discussionmentioning
confidence: 99%
“…La frecuencia de consumo de nutracéuticos fue en su orden: suplementos de vitaminas y minerales, suplementos dietarios, calcio y hierro (19,52,(54)(55)(56)(57)(58)(59).…”
Section: Prevalencia De Consumounclassified
“…Por otra parte, la fabricación cuenta con una deficiente supervisión por parte de entes reguladores en el proceso de producción y distribución, lo que ha permitido que la accesibilidad a este tipo de productos sea muy sencilla, pudiéndose adquirir tanto en farmacias y tiendas especializadas en productos naturales, como en supermercados y negocios independientes. La publicidad, por parte de medios de comunicación y de personal relacionado con el área de la salud, juega un papel importante al momento de fomentar el consumo de nutracéuticos ya que, si bien muchos productos se adquieren a raíz de recomendaciones de profesionales en medicina, gran número de individuos poseen otros motivos que conducen a su consumo; fuentes no relacionadas con el campo de la salud, como los amigos y familiares cercanos, así como los mismos proveedores de los productos, de manera frecuente inducen a las personas a su utilización (59,60).…”
Section: Razones Para El Consumounclassified